Virus clearance methods applied in bioprocessing operations: an overview of selected inactivation and removal methods. (February 2014) - Cameron, Roslyn; Smith, Kate
Viral safety is an integral component of the process design for products derived from biological sources. While each step may contribute to viral safety, specific steps to remove and or inactivate potential viral contamination should be incorporated. The purpose of this article is to provide a brief overview to some of these specific viral clearance steps and how they may be applied in a manufacturing process. Each of these methodologies have a proven ability to remove or inactivate viruses, however selection and implementation of these methods is dependent on a variety of factors beyond the potential reduction achieved. The application of a selected method should be appropriately investigated and characterized before the implementation into the manufacturing process and subsequent viral safety assessment.